Development and diagnostic validation of an ELISA based on an antigenic mixture for the detection of bovine tuberculosis - Griffa, Natanael; Moyano, Roberto Damián; Canal, Ana María; Traveria, Gabriel Eduardo; Santangelo, María De La Paz; Alonso, Maria Natalia; Romano, Maria Isabel (Elsevier, 2020)
Programs for the eradication of bovine tuberculosis (bTB) focus on the tuberculin skin test (TST) and slaughter of reactor cattle. However, the disease remains an animal health concern in several countries and improving the efficiency of the TST has become a critical issue. The detection of Mycobacterium bovis antibodies in serum, within weeks after the TST, may be a rapid and inexpensive way to improve bTB control. This study reports the validation of an enzyme-linked immunosorbent assay (ELISA) to detect bovine tuberculosis as an ancillary test to TST in dairy farms in Argentina.